Zezwierzęcenie świata ludzi. „Nosorożec” Eugène’a Ionesco - Wolska, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents the originality and the timeless meaning of the 1959 Eugène Ionesco play, Rhinoceros which is situated, despite its unambiguous ‘animal’ parable, within the Theatre of the Absurd. In the perspective of the author of the article it is not only Ionesco’s protest against fascism conditioned by the political circumstances which is significant in particular time but the work portraying mechanisms of influence on society, which appears as ‘the masses’, the whole of the society, devoid of any deeper connection with ethical and moral values of humanistic culture, common to all authoritarian ideologies. Among others, the article refers to opinions of scholars of drama and theatre critics on the evolution of Ionesco’s dramatic works and such sociological‑cultural and literary contexts as: 1) José Ortega y Gasset’s thoughts on brutal ‘direct action’ applied to the masses by force factors and on ‘fear of touch’ felt by an individual defending the values of humanistic culture, included in The Revolt of the Masses; 2) plays by Ionesco in which the theme of metamorphosis is important; 3) other works of the Theatre of the Absurd of similar meaning but using different artistic means, Samuel Beckett’s Catastrophe in particular.